Pemberdayaan Masyarakat melalui Inovasi Sirup Jeruk Sehat : Strategi dalam Mengoptimalkan Potensi Produk Lokal - Adi Indradi Wazdi Wazdi; Dandi Muhamad Ramdan Ramdan; Novani Ayu Kartika Kartika; Tyas Septiani Savitri Savitri; Inggi Agusti Agusti (Ma'soem University, 2026)
This community service program was implemented in Karyalaksana Village, Ibun District, Bandung Regency, focusing on processing tangerines into healthy orange syrup as a strategy to increase the added value of local products. The background to this activity was the abundant production of tangerines, which often leads to lower selling prices, so innovation is needed to improve the competitiveness and welfare of farmers. The method used was Community-Based Participatory Research (CBPR) through an intensification approach with PKK women. The activities included technical training ranging from raw material selection, processing, packaging, to calculating the Cost of Goods Sold (HPP) and marketing strategies based on product branding. The results of the activity showed that participants were able to master the skills of making healthy orange syrup independently, understand the importance of cost efficiency, and implement simple marketing strategies to increase sales value. In addition, this program also contributed to increasing entrepreneurial literacy and women's economic participation in the village. Thus, this community service activity not only produces healthy orange syrup products with added value but also has a positive socio-economic impact on the community.